MAPEAMENTO TECNOLÓGICO DE PATENTES DE SIMULADORES DE TIRO - Dall’Agnol, Rogéria Prado; Pires, Edilson Araujo; Santos, Sandra de Andrade; Machado, Gláucio José Couri; Russo, Suzana Leitão (Cadernos de Prospecção, 2016)
Simuladores de Tiro